2019
DOI: 10.1007/s12350-018-1323-7
|View full text |Cite
|
Sign up to set email alerts
|

Infections in patients using ventricular-assist devices: Comparison of the diagnostic performance of 18F-FDG PET/CT scan and leucocyte-labeled scintigraphy

Abstract: F-FDG PET/CT and radiolabeled leucocyte scintigraphy single-photon emission computed tomography carry high performance in the diagnostic of LVAD infections. F-FDG PET/CT shows significantly higher sensitivity and could be proposed as first-line nuclear medicine procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…The most common imaging modalities to date are cardiac ultrasonography or CT imaging to evaluate for device-related infection, however nuclear imaging using positron emission tomography (PET)/CT has now come to the forefront of diagnostic testing. A recently published retrospective study in the Journal of Nuclear Cardiology revealed that PET/CT scanning showed significantly higher sensitivity when compared with radio-labelled leucocyte scan 8. When compared with CT imaging, another prospective study showed that PET/CT imaging was a useful technique for identifying LVAD infection and determining the site and pattern of infection which had significant downstream effects for mortality and patient outcomes 9…”
Section: Discussionmentioning
confidence: 99%
“…The most common imaging modalities to date are cardiac ultrasonography or CT imaging to evaluate for device-related infection, however nuclear imaging using positron emission tomography (PET)/CT has now come to the forefront of diagnostic testing. A recently published retrospective study in the Journal of Nuclear Cardiology revealed that PET/CT scanning showed significantly higher sensitivity when compared with radio-labelled leucocyte scan 8. When compared with CT imaging, another prospective study showed that PET/CT imaging was a useful technique for identifying LVAD infection and determining the site and pattern of infection which had significant downstream effects for mortality and patient outcomes 9…”
Section: Discussionmentioning
confidence: 99%
“…In doubtful cases, white blood cell single-positron emission tomography (WBC-SPECT) can further help define the presence/absence of infection at PVE (11,13,69). In doubtful cases, WBC-SPECT can help define the presence/absence of infection of the pump and cannula (72).…”
Section: Image Analysis and Interpretationmentioning
confidence: 99%
“…de Vaugelade et al [33] compared the diagnostic performance of FDG PET/CT and leucocyte labeled scintigraphy and demonstrated that FDG PET/CT showed greater sensitivity (95.2% vs. 71.4%, respectively). A recent analysis of 57 patients who underwent 85 PET/CT scans showed that a threshold of peak standardized uptake value (SUVpeak) of 2.5 could accurately diagnose driveline infections.…”
Section: Left Ventricular Assist Device Infectionmentioning
confidence: 99%